'n Kritiese evaluering van dr Willie Marais se prediking (Afrikaans) - Pieterse, Hendrik J.C. (Hennie) (University of Pretoria, 2013)
Dissertation (MA (Reasearch in Practical Theology))--University of Pretoria, 2007.